Hubungan Kepercayaan Diri, Tingkat Kecemasan, dan Motivasi Belajar dalam Melaksanakan Teknik Presentasi pada Mahasiswa Keperawatan - Mutiara Maulidinna Sari; Mustopa Mustopa; Rindu Rindu (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
When preparing a presentation plan which includes the ability to recognize the audience, determine objectives, manage the duration and time of the presentation, provide systematic material, complete material content, and prepare oneself to present the material. Self-confidence is defined as a positive attitude to be able to make a positive assessment of the situation one is facing. The level of anxiety is defined as being worried that something undesirable will happen. influence in achieving learning goals for students to determine how difficult and high level of analysis is needed in learning. The aim of this research is to determine the relationship between self-confidence, anxiety level and learning motivation in implementing presentation techniques for nursing students. The design of this research is a descriptive correlation research design and a cross sectional approach with a population of 281 nursing students at the University of Indonesia Maju. The sampling technique used in this research is non-probability sampling with cluster random sampling technique. From the statistical test results, it was found that the positive correlation value was 0.59, P value = 620, positive correlation 0.98 and P value = 419, which means P value > α (0.05). The results of the Ha hypothesis were obtained, namely that there was a relationship between learning motivation and anxiety levels in carrying out presentation techniques among nursing students at Advanced Indonesia University. From the statistical test results, a positive correlation value of 828 was obtained, P value = 0.00, which means P value <α (0.05).